(untitled) (GYMNASIUM, 2009)
In the study of measurements aimed at assessing driving ability for new perspectives of education expressed through integrated education, inclusive education and interdisciplinary. So to work at this age are considered necessary to evaluate the main trends currently learning (integration, interdisciplinarity, etc..). Efficiency problem of the relationship between theory and educational practice in general and the discipline of physical education in particular, is for us an ongoing subject of optimization by focusing equal attention to two aspects of teaching, information and format of transferring specific gravity of educated educated.